CLINICAL SIGNIFICANCE OF NUTRACEUTICALS IN HYPERTENSION: PERSPECTIVES FROM INDIAN RESEARCH - Hardik Agrahari; Vimal Kumar Yadav; Akanksha Singh (GLOBAL JOURNAL OF PHARMACEUTICAL AND SCIENTIFIC RESEARCH, 2026)
Hypertension is a major global health challenge and a leading risk factor for cardiovascular disease, stroke, and renal complications. Despite effective pharmacological treatment, inadequate blood-pressure control and treatment-related limitations have increased interest in complementary approaches. Nutraceuticals, including medicinal plants, vitamins, minerals, fatty acids, polyphenols, probiotics, and functional foods, have demonstrated potential antihypertensive effects through modulation of nitric oxide availability, endothelial function, oxidative stress, inflammation, the renin-angiotensin-aldosterone system, and renal sodium balance. This review focuses on the clinical significance of nutraceuticals in hypertension, with particular emphasis on Indian research and traditional resources such as garlic, amla, moringa, turmeric, fenugreek, and millet-based foods. Available evidence, mechanisms of action, safety, standardization, and potential integration with conventional therapy are discussed. Although several nutraceuticals show promising blood-pressure-lowering effects, variations in dosage, formulation, bioavailability, and clinical study quality remain important limitations. Further standardized, large-scale clinical trials are required to establish their long-term efficacy and safety. Nutraceuticals may therefore serve as useful adjuncts to conventional hypertension management when supported by appropriate clinical evidence.